Japanese Language Teaching And Learning Using Role-Playing Game - Low, Wei Song; Ismail, Zamhar Iswandono; Mohd Suki, Norbayah (2014)
The purpose of this paper is to investigate university students’ perception of role-playing games (RPG) implementation towards conventional teaching and learning approach after undertaking three semesters of Japanese language class. As a part time lecturer for Japanese language course at Universiti Malaysia Sabah-Labuan International Campus, the first author found that some of the students were having difficulties to understand basic Japanese content even after attending Japanese language class for three continuous semesters. With the aim of improving Japanese learning process, this study was carried out towards 27 voluntary Japanese language course students. Students were interviewed and asked to fill an open-ended questionnaire regarding their experience of conventional teaching and learning approach, as well as their perception of RPG implementation for Japanese language learning. Qualitative data analysis method was used along this study. Results indicated that boredom of learning by conventional teaching approach decreases the students’ study motivation. In order to attract the students’ attention towards language learning, students supported the RPG implementation towards conventional teaching approach as it is interesting and increases the students’ study motivation. Throughout the study, it is hoped that the analysis will further improve the Japanese teaching and learning approach in university. As the RPG implementation suggests improving current language learning approach, it aims to produce more undergraduate students who are competitive in terms of language ability. Students were preferably learning Japanese by conventional teaching approach, in addition of RPG implementation towards class lesson. The finding is in fact a good suggestion for the government to reconstruct current varsity teaching and learning approaches in terms of not only Japanese, but other foreign languages learning in public higher educational institutions as it is important to produce high quality graduates with extra foreign language skills.